Potentially Inappropriate Medication (PIM) Prescribing According to Beers Criteria among Elderly Outpatients at Pasar Minggu Hospital, Jakarta - Pebriani, Mala; Sumarny, Ros; Arozal, Wawaimuli; Eviarini, Prawitasari; Ismaya, Nurwulan Adi (Jurnal Kefarmasian Indonesia, 2024)
Elderly patients generally have physiological changes that cause multipathological conditions, so they require several drugs to treat these conditions, it is necessary to evaluate the use of drugs to optimize the treatment of geriatric patients. Beers Criteria 2019 is a criteria that is commonly used to present Potentially Inappropriate Medication (PIM). This study aimed to examine the inaccuracy of prescription drugs in the elderly using Beer's criteria 2019. This research is an observational analytic study with a cross-sectional descriptive design. The Beer's 2019 criteria classify PIM into five categories. Data were taken retrospectively as many as 847 prescriptions met the inclusion criteria at the Pasar Minggu Hospital Outpatient Polyclinic. Data were analysed by Univariate and Bivariate. The results showed that from 847 prescriptions for geriatric patients, there are 160 prescriptions for geriatric patients who experienced PIM (18.89%). Percentage of PIM incidents by category; namely, category 1 was 29.17%, category 2 was 6.77%, category 3 was 44.79%, category 4 was 16.67%, and category 5 was 2.60%. The results of the analysis showed that there was a significant relationship between the number of drugs and Heart Failure and CAD with the incidence of PIM with a p value of 0.000 and 0.035. DM and Heart Failure are 2 diseases that significantly influence the incidence of PIM. This study concludes that the elderly are at risk for receiving potentially inappropriate medications.